Overview Indonesia Tax Ratio in According to Political Agenda and Comparison with Another Country - Fitriani, Azmi; Prasetiyaningsih, Endah; Ameliyaningsih, Tri; Wahono, Puji; Pahala, Indra (Universitas Ibn Khladun Bogor, 2024)
This research was conducted to find out strategies for increasing the tax ratio in Indonesia. The background to this research is that Indonesia has the largest GDP (Gross Domestic Product) in the ASEAN countries, but based on data from the tax ratio of OECD countries, in 2020 tax ratio in Indonesia has decreased from the previous year. The tax ratio in Indonesia in 2019 was 11.59%, while in 2020 it was 10.07%. One of the causes of this is that not all elements of state revenue are included as tax revenue, such as regional taxes.The tax ratio trend in the two governments of the SBY and Jokowi eras tends to decline. The tax ratio achieved in the SBY era was recorded at 13%, while in the Jokowi era it only reached 10.39%. What about the tax ratio agenda in the latest political era in Indonesia and other countries